2010
DOI: 10.1016/j.mce.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

FSH-stimulated PTEN activity accounts for the lack of FSH mitogenic effect in prepubertal rat Sertoli cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.Page 1 of 20A c c e p t e d M a n u s c r i p t AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Acute stimulation of rat testicular Sertoli cells, required for male sexual development, by FSH has been found to increase Pten synthesis and enzymatic activity, thus identifying a new, Pten-dependent mechanism of regulating spermatogenesis 11 . In rats, FSH plasma levels peak between 10 and 15 weeks and decline after this period 12 , which agrees with our findings that, in rat testes, Pten expression increased with maturation from the pre-pubertal (21 days) to the young adult (90 days) stage, but then decreased in the older, middle-aged (180 days) group.…”
Section: Resultssupporting
confidence: 92%
“…Acute stimulation of rat testicular Sertoli cells, required for male sexual development, by FSH has been found to increase Pten synthesis and enzymatic activity, thus identifying a new, Pten-dependent mechanism of regulating spermatogenesis 11 . In rats, FSH plasma levels peak between 10 and 15 weeks and decline after this period 12 , which agrees with our findings that, in rat testes, Pten expression increased with maturation from the pre-pubertal (21 days) to the young adult (90 days) stage, but then decreased in the older, middle-aged (180 days) group.…”
Section: Resultssupporting
confidence: 92%
“…Wu et al demonstrated that PTEN may have a role in the late period of sperm development (18). Dupont et al (19) treated mice with exogenous FSH and estrogen, and reported that FSH controls proliferation and differentiation of Sertoli cells via stimulation of PTEN activity. Moe-Behrens et al (37) reported estrogen exposure induced formation of germ cell testicular tumors via the Akt/PTEN signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al hypothesized that PTEN may have a role in the late stage of sperm development (18). Dupont et al demonstrated that estrogen induced testicular tumors in mice via the PTEN/Akt signal pathway (19). Similarly, Kimura et al revealed that PTEN gene knockout could lead to testicular tumors in mice (20).…”
Section: Introductionmentioning
confidence: 99%
“…FSH has been shown to lead to PI3K activation, PIP3 accumulation, and FSH-dependent proliferation in both granulosa cells and primary Sertoli cells from newborn rat (Park et al, 2005; Musnier et al, 2009; Dupont et al, 2010). Interestingly, in differentiating rat Sertoli cells, PIP3 accumulation is negatively regulated by PTEN whose expression is strongly and rapidly induced upon FSH stimulation, which results in a blockade of FSH-induced proliferation (Dupont et al, 2010). …”
Section: The Pi3k/mtor Pathwaymentioning
confidence: 99%